Artificial Intelligence, School Supervision and School Plant Management in Public Secondary Schools in Abuja, Nigeria - Chogwu, Benjamin Dorcas; Daniel, Adi (MultiTech Publisher, 2024)
The aim of this research was to evaluate how artificial intelligence affects the supervision of schools and the management of school facilities in public secondary schools within the Federal Capital Territory, Abuja, Nigeria. The study utilized a descriptive survey approach, targeting all 292 public senior secondary schools in Abuja. A sample of 400 principals and vice principals was selected using a stratified random sampling method. The research utilized a questionnaire titled